(untitled) (Boletin Médico de Postgrado, 2022)
Pregnancy in adolescents is one of the most common social problems; preventing pregnancy in this stage of life through the use of contraceptive methods is imperative. With the aim of determining the knowledge and use of contraceptive methods in pregnant adolescents who attended the Obstetric Emergency Service of the Hospital Central Universitario Dr. Antonio María Pineda during the month of May 2019, a cross-sectional descriptive study was carried out in 100 pregnant adolescents using a questionnaire prepared by Mallma and validated by experts with a reliability of 0.79; the results revealed the age of the adolescents ranged between 16.6 ± 1.1 years; 64% have incomplete high school and 85% are single; 100% were housewives; 79% lived in the urban sector. 87% and 56% have a good level of knowledge about definition and classification of contraceptive methods, respectively. 71% said that the source of information for knowledge about contraceptive methods was their parents and close relatives. 77% had never used any contraceptive method prior to pregnancy. 87% of patients that used contraception used barrier methods such as condom while 13% use oral contraception.